PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN INDUSTRI PANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020 – 2022 - Karlinadewi, Novi Rahayu; Ambarwati, Ambarwati; Suroso, Bambang; Murni, Sri; Olpah, Hermiliani (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2024)
This study aims to determine the effect of sustainability report disclosure on financial performance carried out by food industry companies listed on the Indonesia Stock Exchange in 2020-2022. The population of this research is food industry companies that are listed on the IDX in 2020-2022. The sample was determined based on the purposive sampling method, as many as 90 companies. The results of the study show that the sustainability report has a positive and significant effect on financial performance. The better the sustainability report, the less negative economic, environmental, social and governance impacts. If sustainability is good, it can increase reputation and brand loyalty.